2019
DOI: 10.1039/c9md00201d
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of [2 + 2 + 2] cyclotrimerisation methodology to prepare tetrahydroisoquinoline-based compounds with potential aldo–keto reductase 1C3 target affinity

Abstract: Tetrahydroisoquinoline (THIQ) is a key structural component in many biologically active molecules including natural products and synthetic pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We are confident that the piezocatalysis methodology is a viable access route to highly functionalized polycyclic derivatives and prompt further discovery of new bioactive compounds. Yields were determined by 19 Chem., 2006, 71, 8028-8036.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are confident that the piezocatalysis methodology is a viable access route to highly functionalized polycyclic derivatives and prompt further discovery of new bioactive compounds. Yields were determined by 19 Chem., 2006, 71, 8028-8036.…”
Section: Discussionmentioning
confidence: 99%
“…16 Schizozygane indoline showed good antimicrobial activity against fungi and bacteria, 17 while Tylophora alkaloids were found to have good hypoxia-inducible factor-1 (HIF-1) and HIV inhibitory activity. 18 A tetrahydroisoquinoline derivative has been used to target AKR1C3, 19 displaying good inhibitory properties for the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of tetrahydroisoquinoline compounds were synthesized with potential AKR1C3 affinity through the [2 + 2 + 2] ring trimerization method. 115 Compared with BBR, the selectivity of compound 14 toward AKR1C2 was improved. Docking analysis results showed that 14 extends into the SP1 and SP3 pockets of AKR1C3 and forms hydrogen bonding interactions in the oxyanion site.…”
Section: Biochemical Assays For the Evaluation Of Akr1c3mentioning
confidence: 99%
“…Recently, a series of tetrahydroisoquinoline compounds were synthesized with potential AKR1C3 affinity through the [2 + 2 + 2] ring trimerization method . Compared with BBR, the selectivity of compound 14 toward AKR1C2 was improved.…”
Section: Development Of Inhibitorsmentioning
confidence: 99%